The History of Legal Regulation of the Injury During the Arrest of the Perpetrator, in Pre-revolutionary Period - Vladlena Alfredovna Ishmuhametova (Сибирское юридическое обозрение)
This paper presents a historical analysis of the regulations dealing with the criminals.